Building an investment portfolio using GARCH - Gutiérrez Urzúa, Mauricio (2012)
In this paper we analyze investment portfolios of Chilean market, using the average model variance proposed by Markowitz, particularly using the variance-covariance matrix of unconditional and conditional, where the latter is estimated through GARCH models. Then, we evaluate the performance of these portfolios using as a reference (benchmark) a market portfolio given by the general index of share prices (IGPA) of Chilean market.